JEWISH WORD SPECIAL EDITION. (Moment Magazine)
The article discuses about the favorite Jewish words. Several discussed include glitch, Abracadabra, tikkun olam, Jewish geography, mensch, and nice Jewish boy. It is reported that Tikkun olam is neither a Torah commandment nor a dictum of the prophets and has the first significant appearance in the Mishnah, the work of oral traditions and laws compiled by rabbis in 200 CE.